Decision makers intention for adoption of Green Information Technology - Asadi, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
Green IT has been considered a panacea for the organization in order to combat the current environmental issue which if not tackled might ultimately hinder the economic growth of an organization. Thus, the adoption of Green IT in the organization is desirable to the society. Consideration for adoption of Green IT by decision makers in an organization will go a long way in encouraging organizations to adopt the technology since the bulk of decision making lies in the hands of business owners otherwise known as decision makers in an organization. However, few literatures have actually addressed these and there is lack of suitable theoretical model for Green IT adoption based on decision makers' intention to adopt Green IT in the organizations. In view of these, the researcher proposed a research model by integrating two theories, Theory of Planned Behavior (TPB) and Norm Activation Theory (NAT). This paper is a research in progress paper which is expected to add to the current knowledge in the field of information systems, to investigate the decision maker's intention for the adoption of Green IT and sustainability. Future research is expected to empirically investigate this proposed model using Smart PLS and SPSS for further analysis. Â© 2016 IEEE.